Performance of Community Based Marine Protected Area in Wakatobi Regency South East Sulawesi - Buhari, Nurliah; Nessa, M Natsir; Ali, Syamsu Alam; Jompa, Jamaluddin (Journal of Indonesian Coral Reefs, 2011)
Community based marine protected area (known nationally in Indonesia as Daerah Perlindungan Laut or DPL) has been established since 2008 as a part of Coremap Phase II in Wakatobi Regency. This research aims to know the DPL performance, in regard with ecology and socio economy aspects ofCOREMAP sites (7 villages). Data collections were conducted during April Â July 2011. The ecological performance was determined through data monitoring coral reef in 2008, 2009 and 2010 from CRITC Wakatobi. The socio-economical performance was measured by interviewing using semi-closed questionnaire to 140 respondents. Research result concludes that life coral cover and fish abundance tend to decrease but not significant. More than half of the respondents (56%) felt that coral reef condition in DPL is better now. That 68% respondent felt the present of DPL had contributed to increase their knowledge on the coral reef ecosystem and decrease blast and poison fishing. However, in terms of increasing the catch and their income, 64 % respondents felt no differences.